A call admission control strategy for integrated services communication systems - Mohamed, Nagla Osman; Deniz, Derviş Z. (My University, 2005)
A multi-server communication system which serves three customer classes is considered. Each customer type i requires b, number of channels for its service. A reserve channels type call admission control strategy is applied to the system and the performance measures of the system are obtained. Within the model, existing two dimensional models have been extended to the three dimensional one. A novel matrix algorithmic technique is developed for solving the global balance equations. The performance measures of this system are compared with that of the complete sharing system.
International Symposium on Performance Evaluation of Computer and Telecommunication Systems 2005, SPECTS 2005, Part of the 2005 Summer Simulation Multiconference, SummerSim 2005 --
Keywords: Broadband node; Call admission control; Integrated services; Matrix algorithmic solution; Performance analysis; Quality of service